Impact of the Covid‐19 pandemic on melanoma and non‐melanoma skin cancer inpatient treatment in Germany – a nationwide analysis. (17th June 2022) - Kleemann, J.; Meissner, M.; Özistanbullu, D.; Balaban, Ü.; Old, O.; Kippenberger, S.; Kloka, J.; Kaufmann, R.; Zacharowski, K.; Friedrichson, B.
Abstract: Background: SARS‐CoV‐2 has massively changed the care situation in hospitals worldwide. Although tumour care should not be affected, initial reports from European countries were suggestive for a decrease in skin cancer during the first pandemic wave and only limited data are available thereafter. Objectives: The aim of this study was to investigate skin cancer cases and surgeries in a nationwide inpatient dataset in Germany. Methods: Comparative analyses were performed in a prepandemic (18 March 2019 until 17 March 2020) and a pandemic cohort (18 March 2020 until 17 March 2021). Cases were identified and analysed using the WHO international classification of diseases codes (ICDs) and process key codes (OPSs). Results: Comparing the first year of the pandemic with the same period 1 year before, a persistent decrease of 14% in skin cancer cases ( n  = 19 063) was observed. The largest decrease of 24% was seen in non‐invasive in situ tumours ( n  = 1665), followed by non‐melanoma skin cancer (NMSC) with a decrease of 16% ( n  = 15 310) and malignant melanoma (MM) with a reduction of 7% ( n  = 2088). Subgroup analysis showed significant differences in the distribution of sex, age, hospital carrier type and hospital volume. There was a decrease of 17% in surgical procedures ( n  = 22 548), which was more pronounced in minor surgical procedures with a decrease of 24.6% compared to extended skin surgery including micrographic surgery with a decrease of 15.9%. Conclusions: Hospital admissions and surgical procedures decreased persistently since the beginning of the pandemic in Germany for skin cancer patients. The higher decrease in NMSC cases compared to MM might reflect a prioritization effect. Further evidence from tumour registries is needed to investigate the consequences of the therapy delay and identify the upcoming challenges in skin cancer care.